Diffusion of low‐molecular‐weight permeants through semi‐crystalline polymers: combining molecular dynamics with semi‐empirical models. Issue 6 (26th March 2018) - Prasad, Krishnamurthy; Nikzad, Mostafa; Doherty, Cara M; Sbarski, Igor
Abstract: A molecular dynamics‐based computational approach was used to study the diffusion of oxygen through a model semi‐crystalline polymer, namely linear low‐density polyethylene. The simulated molecules were validated by comparing the predicted properties with experimental values of available free volumes, on atomic scale, using positron annihilation lifetime spectroscopy and measured values of density. The semi‐crystalline polymer was considered as a composite network of a continuous amorphous phase and a dispersed crystalline phase. Based on this observation, the overall diffusion was simulated, including the diffusion through the crystalline phase, which has not been previously reported. A tight correlation was then achieved between experimental and simulated data by utilising several semi‐empirical and analytical models developed for composite materials. The proposed methodology in this work can be effectively used as a basis for designing polymer networks with controlled diffusion characteristics in a bottom‐up approach. © 2018 Society of Chemical Industry Abstract : Using crystalline and amorphous polyethylene constructed via molecular dynamics, diffusion of oxygen is predicted by combining simulation with mathematical modelling. This novel methodology can be used for bottom‐up design.